PENGARUH PEMBANGUNAN DI ERA GLOBALISASI TERHADAP PEMENUHAN HAK ASASI MANUSIA ATAS LINGKUNGAN HIDUP YANG BAIK DAN SEHAT - Setyo Utomo (UNISSULA, 2014)
Development in the current era of economic globalization has turned out to influence the environmental damage. It certainly has an impact on access to the fulfillment of the human rights guaranteed by the constitution to earn a good living environment and healthy. Every effort has been the development of appropriate attention to the principles of environmental protection laws and sustainable development. Government as a major stakeholder in the obligations of the right to a healthy environment should act progressively in law enforcement efforts in the field of environment and natural resources.